2010
DOI: 10.1002/ajmg.b.31138
|View full text |Cite
|
Sign up to set email alerts
|

Increased symptoms of attention deficit hyperactivity disorder and major depressive disorder symptoms in nail‐patella syndrome: Potential association with LMX1B loss‐of‐function

Abstract: Nail-Patella syndrome (NPS) is an autosomal dominant disorder that is the result of heterozygous loss-of-function mutations in LMX1B, coding for a LIM homeobox (LIM-HD) transcription factor. Analyses of lmx1b mutant mice have revealed the role of Lmx1b in the development of mesencephalic dopaminergic neurons and the serotonergic system; these areas have been linked with symptoms of attention deficit hyperactivity disorder (ADHD) and major depressive disorder (MDD). Fifty adults (38 females, 12 males) with NPS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The latter measures the overall level of ADHD related symptoms. The ADHD index subscale score is seen to be the most reliable and valid estimate of self-reported overall ADHD symptomatology [ 27 , 56 , 57 ]. From the CAARS, an inconsistency index may be calculated that indicates inconsistent responding based on eight pairs of items has similar content; the score is computed by summing the difference scores on each pair.…”
Section: Methodsmentioning
confidence: 99%
“…The latter measures the overall level of ADHD related symptoms. The ADHD index subscale score is seen to be the most reliable and valid estimate of self-reported overall ADHD symptomatology [ 27 , 56 , 57 ]. From the CAARS, an inconsistency index may be calculated that indicates inconsistent responding based on eight pairs of items has similar content; the score is computed by summing the difference scores on each pair.…”
Section: Methodsmentioning
confidence: 99%
“…Given its place, functionally in the serotonergic regulatory network we imagine altered network function in at least some NPS individuals. Although not yet studied in sufficient depth to establish a clear link to neuropsychiatric disease, disrupted LMX1B binding may promote susceptibility to ADHD and major depressive disorder in NPS cases 91 . Further study of this important possibility, including quantitative analysis of disease–associated serotonergic biomarker indices in NPS individuals, is of significant interest in the search for the genetic basis of serotonergic dysfunction in neuropsychiatric disorders.…”
Section: Network Alterations and Pathogenesismentioning
confidence: 99%
“…These proteins are also required for mDA neuron survival, and specific inactivation of Lmx1a/b in adult mDA neurons results in dopamine neuron degeneration and parkinsonism Laguna et al, 2015). Previous studies have shown that a heterozygous loss-of-function mutation in Lmx1b, a LIM homeobox transcription factor, predisposes individuals to exhibit ADHD symptoms (Ló pez-Arvizu et al, 2011). Although animal models cannot fully replicate complex human neuropsychiatric diseases such as ADHD, the specific and conditional knockout (cKO) of the Lmx1a and Lmx1b genes in postmitotic dopaminergic neurons during development results in increased locomotor activity (Doucet-Beaupré et al, 2015).…”
Section: Introductionmentioning
confidence: 99%